Adopting DevOps Practices in Quality Assurance. - ROCHE, JAMES (Communications of the ACM, 2013)
The article considers computer software development and sogtware life cycle management. The obsolescence of the traditional pattern of waterfall development in which development, quality assurance and operations were separate functions, with development and operations now merged into a single function known as DevOps is discussed. It is noted that there is no set definition of DevOps among software engineers. The increased standardization within the computer software industry of the product development process is discussed.